John J. Allen, Don Quijote: hero or fool? A study in narrative technique. University of Florida Press, Gainesville, Fla., 1969; 99 pp. (Univ. of Florida monographs, Humanities, 29). - Aveleyra A., Teresa (El Colegio de México, 1971)
Se reseñó el libro: Don Quijote: hero or fool? A study in narrative technique.